A New Species of Hypostomus (Siluriformes: Loricariidae) from the Upper Rio Paraguay Basin, Brazil - Martins, Fernanda O. [UNESP]; Marinho, Manoela M. F.; Langeani, Francisco [UNESP]; Serra, Jane P. (Amer Soc Ichthyologists & Herpetologists, 2012)
A new small Loricariidae, Hypostomus careopinnatus, is described from the Rio Taquari drainage, upper Rio Paraguay basin, Mato Grosso, Brazil. The new species can be easily distinguished from all congeners, except Hypostomus kids, by the absence of adipose fin. Hypostomus careopinnatus is distinguished from H. levis mainly by the presence of slender bifid teeth, with mesial cusp large and rounded, and lateral cusp small and pointed (vs. spoon-shaped teeth). The new species described herein completely lacks the adipose fin and also lacks the median pre-adipose plates in almost all specimens examined. The absence of adipose fin is probably an independent acquisition for Hypostomus careopinnatus and Hypostomus levis.